KINERJA PEMASARAN JASA DAMPAK TERHADAP LOYALITAS NASABAH - Hamzah, Muhammad Ichwan; Trisasmita, Rio; Pramukty , Rachmat; Hasibuan, Febri D; Arnoldy; Donald, Eriklex (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2025)
This study aims to examine the effect of service marketing performance on loyalty of savers at Bank South Jakarta. The research method used multiple regression and correlation analysis, where the number of samples is determined by using the number of 100 savers. The results showed that the value of correlation (R) of 0.721 which means showing the correlation/strong relationship between People, Process and Physichal Evindenc to Loyalty of the Customer. As for the coefficient of determination seen from the figure on Adjusted R Square of 0.505 it shows that the percentage contribution of independent variables of People, Process, and Physichal Evidence can contribute influence of 50.5% on the dependent variable Customer Loyalty, and the remaining 49.5 % Influenced by other variables not included in this research model.